THE EFFECT OF WORKLOAD AND COMPENSATION ON INPATIENT NURSE TURNOVER INTENTION AT TYPE C HOSPITAL, WEST JAKARTA WITH JOB STRESS AS A MEDIATING VARIABLE - Alexander Yosua Santoso; Bernard T. Widjaja; Wani Devita Gunardi (RADJA PUBLIKA, 2026)
Nurses are professionals who play a crucial role in hospital services, and high turnover intention can impact the quality of healthcare services. Increased workload due to changes in hospital status and suboptimal compensation are suspected to be factors influencing the emergence of job stress and turnover intention. This study used a cross-sectional quantitative approach with a survey method through a questionnaire to inpatient nurses. The data analysis technique used was Smart PLS. The variables studied included workload, compensation, job stress, and turnover intention . The results showed that workload did not have a significant effect on turnover intention directly. However, workload had a significant effect on job stress, and job stress had a positive effect on turnover intention . In addition, compensation had a negative and significant effect on turnover intention and on job stress. Mediation testing showed that job stress was able to mediate the effect of workload on turnover intention , but was unable to mediate the effect of compensation on turnover intention . The conclusion of this study is that job stress is a key variable in explaining the relationship between workload and turnover intention. Meanwhile, compensation has a direct effect on turnover intention without going through job stress. Therefore, hospital management needs to manage workload and work stress effectively and improve the compensation system to control nurse turnover intention .